Práticas de Pré-Jornadinha : a formação do leitor em uma escola rural - Fontana, Maire Josiane (2015)
This study, of empirical social research, consists of an analysis of the activity dimension of Pré-Jornadinha on the reader formation of the students which are in the 8th and 9th grade of Escola Municipal de Ensino Fundamental Francisco Rodrigues dos Santos, a rural school in the city of Água Santa/RS, with emphasis on representations built by students. The two groups together have nine students, but only four of them have a computer at home and only one has internet access. In addition, the school, even with access to the internet, does not allow students to enjoy it. For this study, a bibliographic research based on Judith Langer's theoretical assumptions was developed about the construction of representations and of Michèle Petit and after, an action research which involved, initially, the application of a questionnaire to students with issues related to reading. Based on the answers, it was possible to draw a profile of the participants of this study. The second action of this study occurred with a visit to Mundo da Leitura of the University of Passo Fundo, with the execution of a reading practice with students, aiming the formation of readers in multiple languages. The last action consisted of the development of four reading practices at school involving reading and writing, considering the indicated books for the 7th Jornadinha Nacional da Literatura. The realization of the practices was supported by the 6th booklet of activities of Pré-Jornadinha and books of Mundo da Leitura, which allowed the contact of the surveyed students with innovative and differentiated readings, opening ways for the formation of literary readers including digital support, always in order to motivate them to read and highlight the importance of the teacher as a reference in training and in mediation reader. The work dedicated a depht look at actions of Pré-Jornadinha, in a process of reflection on the reading as a social and literary practice associated with the artistic and cultural manifestations in different media